Cochlodiniinecator piscidefendens gen. nov., sp. nov., an algicidal bacterium against the ichthyotoxic dinoflagellate Cochlodinium polykrikoides. Issue 11 (30th November 2021) - Le, Ve Van; Ko, So-Ra; Lee, Sang-Ah; Jin, Long; Blom, Jochen; Ahn, Chi-Yong; Oh, Hee-Mock
Abstract : Harmful algal blooms caused by Cochlodinium polykrikoides result in enormous economic damage to the aquaculture industry. Biological control methods have attracted wide attention due to their environmental-friendliness. In this study, a novel algicidal bacterium, designated strain M26A2M T, was determined for its taxonomic position and was evaluated for its potential to mitigate C. polykrikoides blooms. Strain M26A2M T exhibited the highest 16S rRNA gene sequence similarity to the type strains of Planktotalea lamellibrachiae (97.3%), Halocynthiibacter namhaensis (97.2%), Pseudohalocynthiibacter aestuariivivens (96.8%) and Halocynthiibacter arcticus (96.4%) in the family Rhodobacteraceae . The predominant fatty acids were C10 : 0 3-OH and summed feature 8 (comprising C18 : 1 ω 7 c and/or C18 : 1 ω 6 c ). The major polar lipids were phosphatidylcholine, phosphatidylglycerol, phosphatidylethanolamine, one unidentified aminolipid and three unidentified lipids. Q-10 was the respiratory quinone. Strain M26A2M T exerted significant algicidal activity against C. polykrikoides cells by destroying the membrane integrity and the photosynthetic system. Our findings suggest that strain M26A2M T shows a high potential to control outbreaks of C. polykrikoides . Based on the polyphasic characterization, strain M26A2M T is considered to represent a novel species within a novel genus of the family Rhodobacteraceae, for which the name Cochlodiniinecator piscidefendens gen. nov., sp. nov. is proposed. The type strain is M26A2M T (=KCTC 82083 T =JCM 34119 T ).